From the four P’s to the four E’s: evangelism - Boyd, Dionne (Henry Stewart Talks, 2024)
Trust, Customer relationships, Viral growth, Marketing techniques, Brands, Unpaid marketing, Social media marketing, Content making, Word of mouth (WOM)